2011
DOI: 10.1186/1471-2377-11-68
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in relapsing remitting multiple sclerosis: A longitudinal study in daily practice using a brief computerized cognitive battery

Abstract: BackgroundThere is need for a cognitive test battery that can be easily used in clinical practice to detect or monitor cognitive performance in patients with multiple sclerosis (MS). In order to conduct, in this patient group, a preliminary investigation of the validity and utility of a brief computerized battery, the Cognitive Drug Research (CDR) battery, we longitudinally assessed cognition in patients with relapsing remitting (RR) MS.MethodsForty-three mildly disabled, clinically active RRMS patients were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 35 publications
1
35
1
Order By: Relevance
“…The system takes approximately 15-20 min to administer and could potentially replace the BRNB and MACFIMS in research and clinical settings where time and administration expertise are an issue. A study comparing the CDR to the PASAT and the Digit Symbol Substitution Test (DSST) alone showed a significant correlation between a composite score and scores from each of the two tests (Edgar et al, 2011). In the same study, most CDR measures had good test-retest reliability ( 40.7), with the exception of working and episodic memory indices.…”
Section: Cognitive Drug Research (Cdr) Batterymentioning
confidence: 96%
“…The system takes approximately 15-20 min to administer and could potentially replace the BRNB and MACFIMS in research and clinical settings where time and administration expertise are an issue. A study comparing the CDR to the PASAT and the Digit Symbol Substitution Test (DSST) alone showed a significant correlation between a composite score and scores from each of the two tests (Edgar et al, 2011). In the same study, most CDR measures had good test-retest reliability ( 40.7), with the exception of working and episodic memory indices.…”
Section: Cognitive Drug Research (Cdr) Batterymentioning
confidence: 96%
“…otherwise not be identified in higher functioning/ lower cognitive impairment base rate populations (Binder, Iverson, & Brooks, 2003;Carey et al, 2004;Edgar et al, 2011;Hinkin et al, 2004;Jak et al, 2009;Sepulcre et al, 2006). Similar to , all impaired scores were summed to create a cognitive impairment index.…”
Section: Neuropsychological Measuresmentioning
confidence: 99%
“…The high rater and patient burden (the MACFIMS taking around 90 minutes to administer) and the high degree of expertise needed to administer, seriously limit the utility of BRNB and MACFIMS in patient care and clinical trials [17]. A recent study reported the preliminary validation of a brief computerized cognitive battery in RRMS [17]. Previous data supported the reliability of the Symbol Digit Modalities Test (SDMT) and the Multiple Sclerosis Neuropsychological Questionnaire (MSNQ) as potential tools for screening and monitoring of cognition in MS [18].…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…Two neuropsychological test batteries have been developed for use in MS patients, the Brief Repeatable Neuropsychological Battery (BRNB) and the Minimal Assessment of Cognitive Functioning in Multiple Sclerosis (MACFIMS) [for brief descriptions see reference 17]. The high rater and patient burden (the MACFIMS taking around 90 minutes to administer) and the high degree of expertise needed to administer, seriously limit the utility of BRNB and MACFIMS in patient care and clinical trials [17]. A recent study reported the preliminary validation of a brief computerized cognitive battery in RRMS [17].…”
Section: Cognitive Impairmentmentioning
confidence: 99%
See 1 more Smart Citation